HUBUNGAN ANTARA KEPEMILIKAN SIM C DAN KEIKUTSERTAAN DALAM TES PEMBUATAN SIM DENGAN PENGETAHUAN BERKENDARA DAN KECELAKAAN LALU LINTAS DI KABUPATEN SIDOARJO - Fadilah Andy Nastiti (The Indonesian Journal of Public Health, 2017)
Traffic accidents are one of the biggest causes of death in the world. WHO states that 90% of deaths that caused by traffic accident in the world occur in low and middle income countries. Indonesia is ranked first with the highest percentage of deaths that caused by traffic accident in Asia. Most t raffic accidents involve motorcyclist with an average age of 15–29 years old. The purpose of this study is to determine the correlation between ownership of driving license and participation in driving license tests with driving k nowledge and t raffic accidents in h igh school students of Xi grade in Kabupaten Sidoarjo in 2017. This research was an observational analytic with cross sectional study design. The population of this study was all senior h igh school students of XI grade in Kabupaten Sidoarjo in 2017. The number of respondents was 204 students that drawn from the population by using two stage cluster random sampling method. Results of analysis using chi square and fisher’s exact test (α = 5%) indicate that the ownership of driving license (p = 0.259; RR 1.533) and participation in driving license test (p = 1.00; RR 0.586) did not have correlation with t raffic accidents in h igh school students of XI grade in Kabupaten Sidoarjo in 2017 and the ownership of driving license (p = 1.00; RR 1.008) and participation in driving license test (p = 1,00; RR 0.983) did not have correlation too with driving k nowledge in h igh school students of XI grades in Kabupaten Sidoarjo in 2017.